Efficient protocol for micropropagation of medicinal forest tree Shyonak (Oroxylum indicum) by silver nitrate promoted high frequency shoot proliferation - Joshi, Neelu; Nailwal, Dr. Tapan Kumar; Dutta, Sharmishtha (Plant Science Today, 2024)
Oroxylum indicum, a significant medicinal plant in the Indian Himalayan Region (IHR), faces ecological and economic challenges due to high demand for its traditional herbal remedies, leading to overexploitation. To combat this, the authors have developed an in vitro propagation protocol aimed at achieving robust shoot proliferation. Using nodal segments from in vitro germinated seedlings, the best results were obtained with a medium containing only benzyladenine (BA) at 22.2 µM. Despite basal callus formation and reduced shoot numbers, the addition of silver nitrate improved shoot proliferation and overall plant health. For in vitro root induction and proliferation, a medium enriched with Indole-3-acetic acid (IAA) at 2.85 µM proved the most effective. Successful transplantation of acclimatized plantlets to field conditions was achieved. This protocol not only aids O. indicum conservation but also holds socio-economic potential for Himalayan communities, as its bark is valuable in commercial Ayurvedic preparations, including Dashamoolarishta.